The latent category of resilience and its relationship with the mental health and coping styles of medical students - Song, Jiang-Yan; Gao, Ya-Qin; Li, Hui-Ping; Gao, Jie; Li, Jia-Xin; Bi, Qing-quan; Li, Shu-Mei; Ye, Yun (Frontiers in Education, 2023)
Objective: To explore the potential categories of resilience of medical students and the relationship between mental health and coping style. Methods: A total of 1,457 medical students in Anhui Province were selected as the research subjects by a convenience sampling method. A general information questionnaire, the Connor-Davidson Resilience Scale(CD-RISC), Kessler 10 and the Simplified Coping Style Questionnaire(SCSQ)were used to investigate; SPSS 25.0 and Mplus 7 software were used for basic analysis and latent category exploration. Expected results: The medical students were divided into three potential categories of mental resilience: the low resilience group, moderate resilience self-improvement group and high resilience tough group. The optimism dimension level of the three categories was low. There were statistically significant differences in the distribution of resilience among medical students, such as gender, source of students, and paternal and maternal education level. There were significant differences in the mental health, positive coping style and negative coping style scores among the three categories. Female medical students with low parental education levels have a lower level of resilience. Logistic regression analysis showed that a lower maternal education level was a risk factor for resilience level, and a high positive coping style score and sex were protective factors for resilience level. Discussion:There are group differences in the resilience of medical students, which suggests that school health workers should formulate targeted intervention programs for different types of students to improve their resilience and mental health.